Apical effect of diosmectite on damage to the intestinal barrier induced by basal tumour necrosis factor-alpha. Issue 3 (March 1997) - Mahraoui, L; Heyman, M; Plique, O; Droy-Lefaix, M T; Desjeux, J F
Abstract : BACKGROUND: In many digestive diseases the intestinal barrier is weakened by the release of proinflammatory cytokines, including tumour necrosis factor-alpha (TNF alpha). AIM: To investigate the protective effect of apical diosmectite on the intestinal dysfunction induced by the proinflammatory cytokine TNF alpha. METHODS: Filter grown monolayers of the intestinal cell line HT29-19A were incubated for 48 hours in basal medium containing 10 ng/ml TNF alpha and 5 U/ml interferon-gamma (IFN gamma). Next, 1, 10, or 100 mg/ml diosmectite was placed in the apical medium for one hour. Intestinal function was then assessed in Ussing chambers by measuring ionic conductance (G) and apicobasal fluxes of 14C-mannitol (Jman), and intact horseradish peroxidase. In control intestinal monolayers, diosmectite did not significantly modify G, Jman, or intact horseradish peroxidase. RESULTS: After incubation with TNF alpha and IFN gamma, intestinal function altered, as shown by the increases compared with control values for G (22.8 (3.7) v (9.6 (0.5) mS/cm2), Jman (33.8 (7.5) v 7.56 (0.67) micrograms/h x cm2), and intact horseradish peroxidase (1.95 (1.12) v 0.14 (0.04) micrograms/h x cm2). G and Jman were closely correlated, suggesting that the increase in permeability was paracellular. Treatment with diosmectite restored al the variables to control values. CONCLUSIONS: Basal TNF alpha disrupts the intestinal barrier through the tight junctions, and apical diosmectite counteracts this disruption.